Analisis Peningkatan Ekonomi Masyarakat Pada Usaha Sanjai di Kecamatan Harau Kabupaten Lima Puluh Kota - Rahma Andriani; Khadijah Nurani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research is based on the obstacles experienced by sanjai owners in Harau District are limited capital, marketing, suppliers who are often stuck or late in coming so that it disrupts the smoothness of the sales process. And also the sanjai problem faced by the sanjai owner himself is the increase in the price of raw materials which causes an increase in sanjai production costs so that it ultimately affects the income of a sanjai cracker entrepreneur.The method of this research is descriptive qualitative. This research is motivated by the decline in sanjai business income during the Covid-19 pandemic. Then also accompanied by an increase in the price of raw materials which resulted in increased production costs so that the selling price also increased. If the seller does not increase the selling price, the business will suffer losses. With the sanjai business, it can improve the community's economy and also open up jobs for people who are not yet working. The way sanjai owners survive in the era of many competitors is to offer lower prices, work with travel drivers and improve service to consumers. The obstacle that sanjai owners also experience is capital. For limited capital, sanjai owners can be assisted by family or seek loans from outside parties.